Peran Guru PAI Dalam Meningkatkan Minat Peserta Didik di SMP Aisyiyah Terpadu Kota Pagar Alam - Sari, Opika; Rahman, Rahman (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to understand the role of Islamic Education Teachers (PAI Teachers) in enhancing students' interest in learning Islamic Education at SMA Terpadu Aisyiyah in Pagar Alam City. The research uses a qualitative approach, conducted through observation and interviews with 15 PAI Teachers and 30 students. The findings indicate that PAI Teachers play a crucial role in increasing students' interest in Islamic Education by creating a positive and engaging learning environment, utilizing interactive teaching methods, and providing opportunities for students to participate in extracurricular activities related to Islamic Education. The study also highlights that the enthusiasm, professionalism, and commitment of PAI Teachers towards their students are key factors contributing to the increased interest in learning Islamic Education. The research concludes that PAI Teachers have a significant role in fostering students' interest in Islamic Education and recommends that school administrators and policymakers support PAI Teachers in developing their teaching skills and expertise in Islamic Education.